Manajemen Nilai Keagamaan dalam Pendidikan Anak Usia Dini: Kajian Literatur - Marika Situmorang; Winda Dewi Listyasari; Mohammad Sofwan Efendi; Kamaludin Kamaludin (Jurnal Pendidikan (Teori dan Praktik), 2026)
Religious programs constitute strategic instruments in early childhood education for fostering children's religious character; however, institutional management often lacks systematic, evidence-based frameworks, resulting in implementation variations and inconsistent character outcomes. This systematic literature review, guided by PRISMA, analyzes national and international studies (2015-2025) to examine how religious programs are designed, implemented, and evaluated for religious character development. Thematic analysis mapped management functions; planning, implementation, leadership, and evaluation, revealing that successful character formation depends on structured planning, educators as religious role models, consistent habituation activities, and continuous evaluation. This review contributes to early childhood education management by offering a comprehensive conceptual framework integrating planning, implementation, leadership, and evaluation for optimizing religious program effectiveness, serving as a foundation for institutional evaluation practices.